Direct Laser Fabrication Method for a Binary Diffractive Optical Element - Kim, Y. G.; Rhee, H. G.; Ghim, Y. S.; Lee, S. Y.; Lee, J. H. (Journal of Advanced Manufacturing Technology (JAMT), 2017)
Binary-type diffractive optics elements (DOEs) are essential components when measuring flow fields. In this paper, a fabrication process for binary-type DOEs was proposed based on direct laser lithography. Two important points must be considered while fabricating DOE . The first was the blurring effect of the lithographic source beam, and the second was the internal spacing issue of the DOE. An effective means of reducing the blurring effect by adjusting the lithography exposure time was suggested. In addition, a method to check the internal spacing was also presented in this paper. A binary-type DOE was successfully fabricated using the proposed process and its optical performance was verified in comparison with the simulation results.